Using of the Policy Analysis Matrix to Assess the Impact of the Syrian crisis on the Citrus Production System - يعقوب, غسان; سليمان, حيان; السفاف, محمد (Latakia University Journal -Biological Sciences Series, 2022)
The aim of the research was to analyze the changes in the citrus support system as a result of the Syrian crisis. For achieving the research objectives, the analysis methodology based on the policy analysis matrix , build on primary data for a sample of 190 farmers randomly collected from citrus farmers in Lattakia during the 2019-2020 agricultural season, in addition To the data of the Agricultural Economy Directorate during the season 2009-2010 and by focusing on the orange crop as a representative of the different types of citrus in general.The results showed that the orange production system during the two study periods has a local competitive advantage because the financial profitability at the local market price is positive, which amounted to about 50,743.9 SP / ha during the first period and 5398520 SP / ha during the second period, but the net effects of this policy were Negative in both periods. Despite the impact of the Syrian crisis, the net impact of the policy has decreased to -1509 SP/ha. In general, the policy of supporting citrus fruits during the crisis period or specifically during the season (2019-2020) did not change substantially compared to the pre-crisis period, but rather witnessed a slight change towards increasing support to farmers, as most indicators of the policy analysis matrix - with the exception of the factors of profitability and effective protection – are Lower than the one before the crisis, this indicates an increase in market distortions during the period of the Syrian crisis, as a result of the government's efforts to support farmers. In addition, it was found that the value of the nominal protection factor is less than one for both seasons, which means that the private prices of the outputs are less than the border prices, and this conclude that farmers will get more profit comparing with the scenario of perfect competition market, hence we conclude that the protection policy on which the citrus production system in Syria is based is unjustified, and the best alternative to these policies is to improve exports and create export market entries to increase the profits of producers.